ENTREPRENEURSHIP AS STRATEGIC RESOURSE: ECONOMIC ESSENCE, MANAGEMENT PROCESSES - P. D. Polovinkin; M. L. Lezina (Модернизация, инновация, развитие, 2016)
At current society development stage, efficient use of entrepreneurship provides for stable production and high living standards. Entrepreneurship is a specific type of economic activities, entrepreneur is a special subject of management. Entrepreneurship’s objective prerequisites and possibilities to get efficiently adapted to postindustrial economic conditions lay in its very essence. Personal and professional qualities of a successful entrepreneur make him effective both as capital owner and manager. The state must create favorable conditions for Russian entrepreneurship.